2007
DOI: 10.1093/nar/gkl1101
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution crystal structure of the intramolecular d(TpA) thymine-adenine photoadduct and its mechanistic implications

Abstract: A high-resolution crystal structure is reported for d(TpA)*, the intramolecular thymine–adenine photoadduct that is produced by direct ultraviolet excitation of the dinucleoside monophosphate d(TpA). It confirms the presence of a central 1,3-diazacyclooctatriene ring linking the remnants of the T and A bases, as previously deduced from heteronuclear NMR measurements by Zhao et al. (The structure of d(TpA)*, the major photoproduct of thymidylyl-(3′-5′)-deoxyadenosine. Nucleic Acids Res., 1996, 24, 1554–1560). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…It was also shown that 8-oxoGua and single-strand breaks are generated with a very low efficiency that is about two to three orders of magnitude lower than that of bipyrimidine photoproducts in cells exposed to UVB radiation (Kielbassa et al 1997;Douki et al 1999;Cadet et al 2012c). It remains to be assessed whether adenine-containing interstrand cross-links that have been characterized in model studies (Wang et al 2001;Davies et al 2007;Asgatay et al 2010;Su et al 2010) are formed in cellular DNA. Increasing interest is being devoted to the photoreactions of 5-methylcytosine at CpG sites because of the implication of methylated cytosine in epigenetic regulation.…”
Section: Formation and Repair Of Uvb-induced Dna Photoproductsmentioning
confidence: 99%
“…It was also shown that 8-oxoGua and single-strand breaks are generated with a very low efficiency that is about two to three orders of magnitude lower than that of bipyrimidine photoproducts in cells exposed to UVB radiation (Kielbassa et al 1997;Douki et al 1999;Cadet et al 2012c). It remains to be assessed whether adenine-containing interstrand cross-links that have been characterized in model studies (Wang et al 2001;Davies et al 2007;Asgatay et al 2010;Su et al 2010) are formed in cellular DNA. Increasing interest is being devoted to the photoreactions of 5-methylcytosine at CpG sites because of the implication of methylated cytosine in epigenetic regulation.…”
Section: Formation and Repair Of Uvb-induced Dna Photoproductsmentioning
confidence: 99%
“…In parallel, we detect the ngerprints of the dimerization reactions. Such reactions are known to occur on the singlet excited state following 254 nm excitation of AT strands, [20][21][22][23] leading to the formation of various photoproducts whose nature is still a matter of debate. 24 Our experimental results are interpreted in the light of quantum mechanical calculations (TD-DFT).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (41,42) have shown that UVC irradiation of DNA strands containing "AATTAA" would produce the AA and TA photoproducts, along with the CPD and PP. However, the AA and TA photochemical yields are at most only 10% of those of TT, making these products much less probable (43,44). The yield of formation of the PP was found to have a sequencedependent photochemistry.…”
Section: Detection Of Uv-induced Dna Photodamage In 96-well Platementioning
confidence: 99%